2014
DOI: 10.1016/j.agwat.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the redistribution and fate of contaminants from soil-injected animal slurry

Abstract: a b s t r a c tSpreading of contaminants from land-applied animal slurry may create hazard for both soil and water environments. Both the leaching and persistence of the contaminants is controlled by the redistribution of the contaminants immediately after application, while the redistribution is influenced by site conditions (here different slurry dry matter content and soil texture). HYDRUS-2D was used to simulate the redistribution of water, chloride, mineral N, Salmonella Typhimurium Bacteriophage 28B (pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 52 publications
(66 reference statements)
0
10
0
Order By: Relevance
“…However, as this current study shows, injecting dairy slurry significantly increases the survival of FIOs in grassland environments compared to broadcast application, potentially sustaining a longer-lasting threat to surrounding water quality if these faecal sources are mobilised and transferred by subsequent rainfall run-off into artificial subsurface drainage systems, known to be efficient conduits of FIO transfer ( Oliver et al., 2005 ). Indeed, some research has highlighted vulnerability of FIO transfers following slurry injection ( Amin et al., 2014 ) and others have suggested that injection actually increases the leaching potential of nitrate, phosphorus and pathogens ( Fangueiro et al., 2014 ). Nevertheless, slurry injection of FIOs into the soil is likely to reduce the risk of ‘incidental’ rapid overland flow losses from land to water following heavy rainfall because the slurry is better protected from detachment mechanisms such as raindrop impact on the soil surface.…”
Section: Discussionmentioning
confidence: 99%
“…However, as this current study shows, injecting dairy slurry significantly increases the survival of FIOs in grassland environments compared to broadcast application, potentially sustaining a longer-lasting threat to surrounding water quality if these faecal sources are mobilised and transferred by subsequent rainfall run-off into artificial subsurface drainage systems, known to be efficient conduits of FIO transfer ( Oliver et al., 2005 ). Indeed, some research has highlighted vulnerability of FIO transfers following slurry injection ( Amin et al., 2014 ) and others have suggested that injection actually increases the leaching potential of nitrate, phosphorus and pathogens ( Fangueiro et al., 2014 ). Nevertheless, slurry injection of FIOs into the soil is likely to reduce the risk of ‘incidental’ rapid overland flow losses from land to water following heavy rainfall because the slurry is better protected from detachment mechanisms such as raindrop impact on the soil surface.…”
Section: Discussionmentioning
confidence: 99%
“…According to knowledge of the longitudinal and transversal dispersivities ( D L and D T ) (Wang, ; Amin et al, ), we used D L = 6 cm and D T = 1 cm for the sandy soil and D L = 12 cm and D T = 1 cm for the sandy loam soil. Molecular diffusion ( D w ) involved in the simulation was determined according to the values reported by Ford and Harvey ().…”
Section: Resultsmentioning
confidence: 99%
“…The description of the simulation process is brief here because it was not the main focus of the study. This type of simulation study using HYDRUS model has been described in Amin et al (2014).…”
Section: Data Simulationmentioning
confidence: 99%